2015
DOI: 10.7554/elife.05856
|View full text |Cite
|
Sign up to set email alerts
|

Expression noise facilitates the evolution of gene regulation

Abstract: Although it is often tacitly assumed that gene regulatory interactions are finely tuned, how accurate gene regulation could evolve from a state without regulation is unclear. Moreover, gene expression noise would seem to impede the evolution of accurate gene regulation, and previous investigations have provided circumstantial evidence that natural selection has acted to lower noise levels. By evolving synthetic Escherichia coli promoters de novo, we here show that, contrary to expectations, promoters exhibit l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 42 publications
11
80
0
1
Order By: Relevance
“…The intrinsic noise term decreases with the mean total cell fluorescence (Fig. 4b) until a noise floor is reached at high mean concentrations 26, 28 . This noise floor is thought to arise from sources of noise that do not directly scale with volume, such as fluctuations in the concentration of transcription and translation machinery 29, 31 .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The intrinsic noise term decreases with the mean total cell fluorescence (Fig. 4b) until a noise floor is reached at high mean concentrations 26, 28 . This noise floor is thought to arise from sources of noise that do not directly scale with volume, such as fluctuations in the concentration of transcription and translation machinery 29, 31 .…”
Section: Resultsmentioning
confidence: 93%
“…Data suggest that fluctuations in the concentrations of transcription and translation machinery, or translational burst size, may be involved 2931 . This noise-vs-mean scaling is found regardless of whether protein expression is quantified as total fluorescence per cell, molecule copy number or concentration 2628 .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although transcription is a complicated system intertwined with many regulatory factors, especially in eukaryotic cells, we note that the multi-subunit RNAPs such as RNAP, which play the central role in transcription of all organisms, are highly conserved and, presumably, the regulation of the elongation process was achieved earlier in evolution than the initiation process24. Furthermore, a recent study suggested that gene regulation evolved, because it increases gene expression noise and benefits an organism as a result25. We believe that because transcriptional bursting (gene expression noise), which leads to cell-to-cell variability, benefits an organism without regulation of initiation, it is plausible that our model is the most evolutionarily primitive mechanism associated with elongation that is responsible for the gene-nonspecific kinetics seen in contemporary organisms.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, a recent analysis of a synthetic promoter library evolved de novo revealed that, while initial promoter noise levels are generally low, selective pressure placed on these regulatory sequences routinely results in increased expression noise. Promoter-associated noise is further propagated by noise associated with regulators, and may act as the primary step to the evolution of more finely tuned regulation (17).…”
Section: Lessons From Bacteria I: the Role Of Noisementioning
confidence: 99%